2010
DOI: 10.1175/2009jtecha1320.1
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Calibration of Hot-Film Probes Using a Collocated Sonic Anemometer: Implementation of a Neural Network

Abstract: Although the integral quantities of atmospheric turbulence are conveniently measured using sonic anemometers, obtaining relevant finescale variables such as the kinetic energy dissipation using conventional hot-film/wire techniques remains a challenge because of two main difficulties. The first difficulty is the mean wind variability, which causes violation of the requirement that mean winds have a specific alignment with the hot-film/wire probe. To circumvent this problem, a combination of collocated sonic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 23 publications
1
60
1
Order By: Relevance
“…Integrating the spectrum up to f ¼ f r , we find that TKE is underestimated in lidar measurements by about 7% for the ARL lidar, and 11% for the UU lidar compared with the sonic anemometer. Analogously, the work of Kit et al 40 showed that about 10% of the energy is unaccounted for due to the relatively low resolution of sonic anemometers compared to hot-film probes.…”
Section: Observations Of Large Turbulent Motions Using Dual Doppler Wmentioning
confidence: 89%
“…Integrating the spectrum up to f ¼ f r , we find that TKE is underestimated in lidar measurements by about 7% for the ARL lidar, and 11% for the UU lidar compared with the sonic anemometer. Analogously, the work of Kit et al 40 showed that about 10% of the energy is unaccounted for due to the relatively low resolution of sonic anemometers compared to hot-film probes.…”
Section: Observations Of Large Turbulent Motions Using Dual Doppler Wmentioning
confidence: 89%
“…The measurements at dissipation scales of SBL remain a challenge because of the low resolution of commonly used probing instruments as well as the changing wind direction and calibration requirements that stymie the use of high-resolution probes such as hot wire/film anemometers. New techniques have been developed to address these issues (Kit et al 2010), which offer promise for delving into SBL dissipation scales. As such, capabilities are becoming available to probe SBL on scales from tens of kilometers to millimeters, and future field experiments must fully capitalize on such multiscale probing capabilities.…”
Section: E V E Lo Pm E Nt a N D D E Ploy M E Nt Challengesmentioning
confidence: 99%
“…The flow velocity and, if required, the flow direction are systematically changed over a parameter range of interest, thus obtaining input points that are separated at regular intervals. The standard tool for predicting the voltage-velocity relations in this case is polynomial least squares fit (PF; e.g., Kit et al 2010, and references therein). However, obtaining such calibration curves in the atmosphere has been a problem, given the difficulty of calibrating in unfriendly outdoor environments and the necessity for frequent calibrations in view of slowly changing probe performance resulting from contamination.…”
Section: Introductionmentioning
confidence: 99%